Ber-EP4: new monoclonal antibody which distinguishes epithelia from mesothelial. - Latza, U (1990)
A new monoclonal antibody, Ber-EP4, directed against a partially formol resistant epitope on the protein moiety of two 34 kilodalton and 39 kilodalton glycopolypeptides on human epithelial cells is described. Immunostaining of a wide range of normal and neoplastic human tissues and cell lines showed that all carcinomas and all non-neoplastic epithelial cells, except hepatocytes, parietal cells, and apical cell layers in squamous epithelia, homogeneously expressed Ber-EP4 antigen. As Ber-EP4 does not detect any normal or neoplastic non-epithelial cells, this antibody might prove valuable for the differentiation of the following (i) non-epithelial tumours from undifferentiated carcinomas; (ii) hepatocytes from bile duct cells in certain liver diseases; (iii) mesothelial cells from carcinoma cells in lung biopsy specimens; and (iv) reactive mesothelial cells from carcinoma cells in smears of serous effusions.